Incomes policies; some foreign experiences and their relevance for Canada - Smith, David C.; Economic Council of Canada (Ottawa R. Duhamel, Queen's printer and controller of stationery, 1966)
This book explores the question of what Canada can learn from recent foreign experience with incomes policy but a few points of caution are in order at the outset.
.
Includes bibliographies
osa; 21/6/17
Loans
Keywords: Economic policy - Case studies; Prices - Case studies